On the relationship between surface tension and viscosity of fluids - Ahmari, Hadi; Amiri, Mohammad Chalkesh (Chemical Engineering Research Bulletin, 2016)
Relating surface tension and viscosity of liquids not only is important conceptually but it can also be used to test the validity of some measured data. Schonhorn modified Pelofskys equation by introducing the concept of the vapor viscosity ?v in equilibrium with the liquid, i.e.?= Aexp(-B/(?l-?v)) This empirical relation can be applied to both organic and inorganic solutions of pure and mixed components. As surface tension is a strong function of surfactant, they neglected to emphasis that mixed components must not be surface active agents. Both Pelofsky and Schonhorn indicated that A may be an indication of the surface tension of the liquid at the temperature where ?=?. They were not successful in correlating the temperature where and the surface tension at the melting point. In this work, a new empirical equation for relating surface tension and viscosity has been developed, i.e., ?((Tc Tm)/( Tc T)) = ?(1-?/?). This equation not only satisfies the extreme conditions but it also reveals a physical concept for ?, that is, it should equal the surface tension at the melting point of the liquid. Chemical Engineering Research Bulletin 18(2015) 18-22